Effect of high-quality nursing model on rehabilitation of patients with cerebral hemorrhage caused by cerebral vascular malformations (优质护理模式在脑血管畸形出血患者康复中的应用效果) - LI Yunmeng (李云梦) (Association of Integrative Nursing, 2023)
Objective To investigate the effect of high-quality nursing mode on the rehabilitation of patients with cerebral hemorrhage caused by cerebral vascular malformations. Methods Totally 120 patients with cerebral hemorrhage caused by cerebral vascular malformations admitted to hospital from January 2021 to December 2022 were randomly divided into two groups. The control group was given routine nursing, and the observation group was given high-quality nursing mode. The length of stay, rehabilitation effect, nursing satisfaction, psychological state, complications, nursing quality score and quality of life of the two groups were analyzed. Results The length of hospital stay in observation group was shorter than control group (P＜0. 05). The scores of Self-rating Anxiety Scale and Self-rating Depression Scale in the observation group were lower than those in the control group after intervention(P＜0. 05). Totally rehabilitation rate and nursing satisfaction rate of the observation group were significantly higher than those of the control group (P＜0. 05), and the incidence of compilations in the observation group was lower than that in the control group (P＜0. 05). Scores of nursing quality assessment and quality of life evaluation scale in the observation group were significantly higher than those of the control group(P＜0. 05). Conclusion The application of high-quality nursing mode is potentially effective to relieve the negative emotion and improve the recovery and patients' quality of life. (目的 探讨优质护理模式在脑血管畸形出血患者康复中的应用效果。方法 120例脑血管畸形出血患者随机分为观察组和对照组, 各60例。对照组实施常规护理, 观察组给予优质护理模式, 观察两组住院时间、心理状态、康复效果、护理满意度、并发症生情况、护理质量评分以及生活质量。结果 观察组住院时间短于对照组, SAS、SDS评分低于对照组, 差异有统计学意义(P＜0. 05); 观察组康复效果、护理满意度均优于对照组, 并发症发生率低于对照组, 差异有统计学意义(P＜0. 05); 观察组护理质量以及生活质量各维度评分均高于对照组, 差异有统计学意义(P＜0. 05)。结论 对脑血管畸形出血患者应用优质护理模式, 有助于改善负性情绪, 提高生活质量, 促进患者早日康复, 值得推广和应用。)